Casim Coffee Business Development Strategy in Karangpring Village, Sukorambi District, Jember Regency - Utami, Bening; Ismail, Andi Muhammad (Politeknik Negeri Jember, 2024)
Casim Coffee Business, a microenterprise in Jember Regency, requires development to enhance its operations. This study aims to: (1) identify and analyze internal and externsal factors influencing the strengths, weaknesses, opportunities, and threats in the development of Casim Coffee Business in Karampling Village, Skollambi District, Jember Regency; (2) formulate alternative strategies for business development; and (3) determine strategic priorities for implementation. The study employs IFE Matrix, EFE Matrix, SWOT Analysis, and QSPM Matrix methodologies. The IFE Matrix yielded a score of 2.882, while the EFE Matrix scored 2.760. According to the IE Matrix, the business is positioned in cell V, which corresponds to a